The occurrence and distribution of resistance of codling moth to Cydia pomonella granulovirus in Europe. (11th March 2013) - Schmitt, A.; Bisutti, I. L.; Ladurner, E.; Benuzzi, M.; Sauphanor, B.; Kienzle, J.; Zingg, D.; Undorf‐Spahn, K.; Fritsch, E.; Huber, J.; Jehle, J. A.
Abstract: Thirty‐five codling moth (CM, Cydia pomonella L., Lepidoptera, Tortricidae) populations collected in different commercial orchards in six European countries were tested for their susceptibility to Cydia pomonella granulovirus (CpGV‐M). Including previously published data on CpGV‐M resistance, a total of 38 CM colonies showed considerably elevated LC50 values, independent of the country origin. When only few test individuals are available, determination of mortality of neonate larvae at a discriminating concentration range of 10 4 to 10 6 OB/ml (>log4) as a direct measure of percentage susceptible individuals in a CM population is more advisable than calculation of LC50 values. The >log4 mortality alone or in combination with the LC50 value can be used for identification of resistance in a population. Results indicated a locally separated but widely spread occurrence of CM populations with low susceptibility to CpGV‐M. The most plausible hypothesis for the emergence of CpGV‐M resistance is its selection by repeated use of CpGV products.